A basic, positively charged silica sol and a method for its preparation
Patent Information
- Application Number
- CN202611030927.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-09
AI Technical Summary
例如,单独使用硅烷偶联剂KH792虽然可以通过端氨基与硅醇基团形成Si-O-N或Si-O-Si的化学键合,但单一体系下的静电斥力提升有限,往往难以满足高碱性条件下的正电荷需求
(1)本发明通过采用硅烷偶联剂KH792与阳离子改性剂的分步联合改性工艺,在特定的温度条件(90℃)下,使气相二氧化硅颗粒表面形成了结构致密、电荷密度高且稳定性优异的改性层。本发明通过分步改性,成功实现了颗粒表面的强电荷翻转,在强碱性环境(pH=8-11)下依然能够保持+25mV以上的Zeta电位,有效解决了传统硅溶胶在碱性环境中无法实现正电荷功能化的技术难题。
Smart Images

Figure CN122877762A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silica sol preparation technology, and relates to an alkaline positively charged silica sol and its preparation method. Background Technology
[0002] Fumed silica, as an extremely important inorganic non-metallic nanomaterial, occupies a pivotal position in colloid chemistry, rheological modification, catalyst support, and high-performance coatings due to its extremely high specific surface area, unique branched structure, and abundant surface hydroxyl groups (-OH). In practical applications, fumed silica usually exists in the form of silica sol, and the stability, flowability, and surface charge characteristics of its dispersion system directly determine the final quality and application performance of downstream industrial products.
[0003] However, unmodified fumed silica particles, due to the large number of silanol groups (Si-OH) on their surface, often exhibit low absolute Zeta potential values in aqueous media, or are prone to agglomeration under specific acidic or alkaline conditions, resulting in problems such as drastically increased slurry viscosity, low density of the formed green body, or poor dispersion stability. Especially in industrial slip casting and CMP (chemical mechanical polishing), the density of RSiC ceramic green bodies is directly related to the flowability of its slurry, which in turn is controlled by the agglomeration state of nanoparticles in the liquid. Therefore, improving the dispersion stability of ultrafine particles in aqueous phase through surface modification has become a key technical step in enhancing product performance.
[0004] Existing surface modification technologies are mainly divided into physical adsorption methods and chemical grafting methods. Traditional physical modification methods typically use simple surfactants for encapsulation, which can reduce viscosity to some extent. However, due to the weak physical adsorption force, the modified layer is prone to detachment under high-speed shear, temperature fluctuations, or strong acid / alkali environments, causing the silica sol system to rapidly lose stability and exhibit severe "flipping effect" or gelation. On the other hand, while relying solely on a strongly alkaline environment can induce some electrostatic repulsion, without sufficient steric hindrance synergy, the electrostatic stabilization effect alone is insufficient to maintain the long-term fluidity of the system at high solid content (e.g., 51 vol%).
[0005] In recent years, chemical modification methods, represented by silane coupling agents, have made significant progress. For example, CN102040868A discloses a method for preparing alkaline silica sol and its surface modification, which involves adding silane coupling agent KH560 to silica sol, resulting in a modified silica sol with a pH value between 9 and 11.5, allowing for long-term stable storage. However, many challenges remain in actual industrial preparation. For instance, while using silane coupling agent KH792 alone can form Si-ON or Si-O-Si chemical bonds with silanol groups through terminal amino groups, the improvement in electrostatic repulsion in a single system is limited, often failing to meet the positive charge requirements under highly alkaline conditions.
[0006] Therefore, there is an urgent need for a method to prepare positively charged silica sols with high zeta potential and excellent long-term dispersion stability under alkaline conditions. Summary of the Invention
[0007] The purpose of this invention is to overcome the above-mentioned defects of existing chemical modification methods, and thus provide an alkaline positively charged silica sol and its preparation method.
[0008] The objective of this invention can be achieved through the following technical solutions: One of the technical solutions of the present invention is to provide a method for preparing alkaline positively charged silica sol, comprising the following steps: S1. Prepare a silica aqueous dispersion by mixing fumed silica with water; S2. Under stirring, the silica aqueous dispersion from step S1 is heated, and N-2-aminoethyl-3-aminopropyltrimethoxysilane coupling agent is added to carry out the reaction. S3. Continue to add cationic modifier to the system from step S2 to carry out the reaction; S4. After the reaction is complete, adjust the pH of the system from step S3 to 8-11 to obtain an alkaline positively charged silica sol.
[0009] In some specific embodiments, in step S1, the solid content of the silica aqueous dispersion is 8% to 15%.
[0010] In some specific embodiments, step S2 involves heating the silica aqueous dispersion to 50~90°C; The reaction was carried out with N-2-aminoethyl-3-aminopropyltrimethoxysilane coupling agent for 2-5 h.
[0011] In some specific embodiments, in step S2, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane coupling agent to fumed silica is 1:30-1:5.
[0012] In some specific embodiments, in step S3, the cationic modifier is a polymer containing a quaternary ammonium salt structure or an amino structure.
[0013] In some specific embodiments, in step S3, the cationic modifier is selected from at least one of polydimethyldiallylammonium chloride (PDADMAC), polyethyleneimine, and polyepoxychloropropane-dimethylamine.
[0014] In some specific embodiments, in step S3, the mass ratio of the cationic modifier to fumed silica is 1:20 to 1:2.
[0015] In some specific implementations, the reaction time for step S3 is (2~4) h.
[0016] In some specific implementations, step S4 involves adding an inorganic base to adjust the pH.
[0017] The second technical solution of the present invention is to provide an alkaline positively charged silica sol, which is obtained by the preparation method described in one of the above technical solutions. The average particle size of the alkaline positively charged silica sol is 80-150 nm, and the Zeta potential is maintained above +25 mV at pH=10.
[0018] This invention utilizes an electrostatic-steric stabilization mechanism, which combines the covalent anchoring effect of silane coupling agents with the electrostatic shielding and repulsion effects (electrostatic reversal and steric hindrance effects) of cationic polymers, to solve the problem of ultrafine powder dispersion.
[0019] The silane coupling agent used in this invention is KH792 (N-2-aminoethyl-3-aminopropyltrimethoxysilane). The chemical anchoring effect of KH792 provides "sites" and initial charge reversal for the subsequent adsorption of the cationic modifier. Through "stepwise reaction" and "temperature control," the hydrolysis and condensation of the silane coupling agent and the physical adsorption of the cationic modifier occur disorderly within the same timeframe when stepwise feeding control is lacking. This results in irregular arrangement of modified molecular chains on the particle surface, failing to form a dense and stable coating layer, and thus causing poor stability of the slurry system during long-term storage. Therefore, this invention can induce the formation of an ordered bilayer structure of "chemical bonding layer + electrostatic coating layer" on the particle surface, obtaining a positively charged silica sol product with high zeta potential, low viscosity, and excellent long-term dispersion stability in an alkaline environment (pH 8-11). This product possesses a stable three-layer structure of "core-anchoring layer-coating layer," providing reliable technical support for the military, semiconductor, and precision ceramics manufacturing fields.
[0020] The terminal amino groups generated after KH792 hydrolysis interact with the silanol groups on the silica surface via hydrogen bonding, further dehydrating and condensing to form Si-O-Si or Si-ON bonds. This covalent bonding ensures the stability of the modified layer under extreme environments. The long organic chains of KH792 provide the first layer of steric hindrance, while the subsequently introduced cationic modifiers (such as PDADMAC) coat the particle surface through strong electrostatic attraction. Under alkaline conditions, a high-density positively charged layer forms on the particle surface, generating a strong electrostatic repulsion force. Combined with the steric hindrance effect of the polymer chains, this effectively prevents the aggregation of silica particles. Therefore, adding KH792 for surface treatment can effectively reduce the initial aggregation degree between silica particles, laying the foundation for the subsequent uniform coating of polymeric electrolytes.
[0021] The experiments conducted in this invention have shown that 90℃ is the ideal temperature for the condensation reaction between KH792 and the hydroxyl groups on the surface of silica. This temperature ensures the reaction rate while preventing the solvent from evaporating too quickly, which could lead to inaccurate solid content.
[0022] Compared with the prior art, the present invention has the following advantages: (1) This invention employs a stepwise combined modification process using silane coupling agent KH792 and a cationic modifier to form a dense, high-charge-density, and highly stable modified layer on the surface of fumed silica particles under specific temperature conditions (90°C). Through this stepwise modification, the invention successfully achieves strong charge reversal on the particle surface, maintaining a Zeta potential above +25mV even in a strongly alkaline environment (pH=8-11), effectively solving the technical challenge of traditional silica sols failing to achieve positive charge functionalization in alkaline environments.
[0023] (2) Unlike simple physical adsorption, KH792 in this invention first forms a chemical bond (Si-O-Si / Si-ON) with the silanol groups on the particle surface, forming a strong interfacial connection. This covalent bond ensures that the subsequent coated cationic polymer is not easily detached under extreme shear force and environmental pH fluctuations, greatly extending the storage period and service life of the silica sol.
[0024] (3) The silica sol prepared by the present invention has the advantages of alkaline positive charge properties and excellent dispersibility. It has high application value in precision chemical mechanical polishing (CMP), functional coating, high-performance ceramic preparation and papermaking additives, effectively meeting the special requirements of downstream materials for interfacial activity and charge distribution. Attached Figure Description
[0025] Figure 1 Particle size distribution of fumed silica before and after modification: Figure A shows the particle size distribution before modification, Figure B shows the particle size distribution after modification, and Figure C shows the particle size distribution after modification and standing for 30 days.
[0026] Figure 2 Zeta potential diagram of the alkaline positively charged silica sol prepared in this invention. Detailed Implementation
[0027] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0029] Unless otherwise specified, the materials and processes described in the following embodiments or examples are conventional materials and processes used in the art to achieve the corresponding functions.
[0030] Example 1: This embodiment provides an alkaline positively charged silica sol, which includes the following preparation steps: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0031] (2) Modification: The suspension was heated to 90°C. 1 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 3.5 hours. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 3 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0032] Test results: The obtained silica sol system with a Zeta potential of +77.9mV showed no sedimentation during the 30-day observation period, demonstrating excellent colloidal stability, proving that the charge properties were successfully controlled under these conditions.
[0033] Example 2: Compared with Example 1, most of them are the same, except that the amount of KH792 and PDADMAC used in step (2) is increased.
[0034] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0035] (2) Modification: The suspension was heated to 90°C. 2 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 3.5 hours. 3 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 3 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0036] The zeta potential of the sample was measured to be +83.4 mV.
[0037] Example 3: Compared with Example 1, most of them are the same, except that the amount of KH792 and PDADMAC used in step (2) is reduced.
[0038] The specific steps are as follows: This embodiment provides an alkaline positively charged silica sol, which includes the following preparation steps: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0039] (2) Modification: The suspension was heated to 90°C. 0.5 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 3.5 hours. 0.75 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 3 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0040] The zeta potential of the sample was measured to be +35.1 mV.
[0041] Example 4: The two examples are largely the same as in Example 1, except that the temperature in step (2) is replaced with "50°C".
[0042] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0043] (2) Modification: The suspension was heated to 50°C. 1 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 3.5 hours. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 3 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0044] The zeta potential of the sample was measured to be +43.3 mV.
[0045] Example 5: The two examples are largely the same as in Example 1, except that the temperature in step (2) is replaced with "70°C".
[0046] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0047] (2) Modification: The suspension was heated to 70°C. 1 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 3.5 hours. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 3 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0048] The zeta potential of the sample was measured to be +54.7 mV.
[0049] Example 6: Compared with Example 1, most of them are the same, except that the reaction time with KH792 in step (2) is adjusted to 2.5 h and the reaction time with PDADMAC is adjusted to 2 h.
[0050] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0051] (2) Modification: The suspension was heated to 90°C. 1 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 2.5 hours. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 2 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0052] The zeta potential of the sample was measured to be +55.9 mV.
[0053] Example 7: Compared with Example 1, most of the results are the same, except that the reaction time with KH792 in step (2) is adjusted to 4.5 h and the reaction time with PDADMAC is adjusted to 4 h.
[0054] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0055] (2) Modification: The suspension was heated to 90°C. 1 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 4.5 hours. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was carried out under continuous stirring for 4 hours to ensure that the polymer chains formed a dense positively charged coating layer on the particle surface, thus obtaining an alkaline positively charged silica sol.
[0056] Measurements showed that, due to the extended reaction time, the chemical bonding and surface adsorption approached saturation, and the zeta potential of the sample increased to +71.9 mV.
[0057] Comparative Example 1: Compared with Example 1, most of them are the same, except that PDADMAC in step (2) is omitted.
[0058] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0059] (2) Modification: The suspension was heated to 90°C. 1 g of silane coupling agent KH792 was slowly added dropwise under continuous stirring, and the reaction was carried out at a constant temperature for 3.5 hours to obtain modified silica sol.
[0060] Measurements showed that without the synergistic coating of a polymeric electrolyte, the system's ability to maintain positive charge under alkaline conditions using only a single coupling agent was extremely poor, with the sample's Zeta potential being only +5.4 mV.
[0061] Comparative Example 2: Compared with Example 1, most of them are the same, except that the silane coupling agent KH792 in step (2) is omitted.
[0062] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0063] (2) Modification: The suspension was heated to 90°C. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was added under continuous stirring, and the reaction was continued for 3 hours to obtain modified silica sol.
[0064] Due to the lack of chemical covalent anchoring effect of silane coupling agent on the particle surface, the polymer chain relies only on weak physical electrostatic adsorption, and is very prone to desorption due to counterion shielding in a highly alkaline environment. The zeta potential of the sample is only +17.3 mV.
[0065] Comparative Example 3: Compared with Example 1, most of them are the same, except that the silane coupling agent KH792 and PDADMAC added in batches in step (2) are mixed first and then added all at once.
[0066] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0067] (2) Modification: The suspension was heated to 90°C. Under continuous stirring, 1 g of silane coupling agent KH792 and 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) were mixed uniformly in advance and then added to the reaction system at the same time. The reaction was carried out under continuous stirring at 90°C for 3.5 h to obtain modified silica sol.
[0068] This process disrupts the ordered structure of the stepwise reaction. Due to the mutual interference between the self-condensation of the coupling agent and the competitive adsorption of the monomer, a dense coating layer cannot be formed, and the zeta potential of the sample fails to flip, with a measured value of -2.9 mV.
[0069] Comparative Example 4: Compared with Example 1, most of them are the same, except that the silane coupling agent KH792 and PDADMAC added in batches in step (2) are replaced with L-arginine.
[0070] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0071] (2) Modification: The suspension was heated to 90°C. 1 g of small molecule L-arginine was added under continuous stirring to obtain modified silica sol.
[0072] Because small molecule amino acids dissociate their carboxyl groups and become negatively charged under alkaline conditions, the zeta potential of the sample is -30.8 mV.
[0073] Comparative Example 5: Compared with Example 1, most of them are the same, except that the silane coupling agent KH792 in step (2) is replaced with L-arginine.
[0074] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0075] (2) Modification: The suspension was heated to 90°C. 1 g of L-arginine was slowly added dropwise while stirring continuously, and the reaction was carried out at a constant temperature for 3.5 hours. 1.5 g of polydimethyldiallylammonium chloride (PDADMAC) was then added, and the reaction was continued with stirring for 3 hours to ensure that the polymer chains formed a dense positive charge coating layer on the particle surface, thus obtaining the modified silica sol.
[0076] Due to the lack of covalent bonding with silane coupling agents and the electrostatic antagonism between arginine and the polymer, the zeta potential of the sample was -29.1 mV.
[0077] Comparative Example 6: The difference compared to Example 1 lies in the modification of step (2).
[0078] The specific steps are as follows: (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0079] (2) Modification: Under stirring, 3 g of 1 mol / L HCl and 20 g of 10% aluminum chloride were added dropwise to the above uniform suspension. The mixture was reacted at 65°C for 1.5 h. Then, 25% tetrapropylammonium hydroxide was added to adjust the pH to 8 to obtain modified silica sol.
[0080] Due to the lack of steric hindrance protection from the polymer chains, the inorganic aluminum salt hydrolyzes to form a precipitate in an alkaline environment, and the zeta potential of the sample is only +4.78 mV.
[0081] Comparative Example 7: The difference compared to Example 1 lies in the modification of step (2).
[0082] (1) Slurry preparation: Weigh 10 g of fumed silica (white carbon black), add 90 g of deionized water, and stir at 3000 rpm for 40 minutes under a high-speed shear machine to prepare a uniform suspension with a solid content of 10%.
[0083] (2) Modification: Under stirring, 10 g of ethylene glycol and 20 g of 10% aluminum chloride were added to the dispersion, and the mixture was reacted at 65°C for 1.5 h. Then, 25% tetrapropylammonium hydroxide was added to adjust the pH to 9 to obtain modified silica sol.
[0084] Measurements showed that the system could not produce effective charge reversal under strongly alkaline conditions, and the zeta potential of the sample was -6.6 mV.
[0085] The modified silica sol prepared above was subjected to the following performance tests: (1) Measurement of Zeta potential and pH value The surface charge of the prepared silica sol samples was tested using a laser colloidal particle size and zeta potential analyzer. Before testing, the silica sol samples were diluted with deionized water to a suitable concentration, and the current pH value of the system was monitored and recorded in real time using a high-precision pH meter. Under a specific alkaline environment (pH=8-11), the zeta potential (mV) was measured in the test cell to evaluate the degree of charge reversal and electrostatic repulsion effect on the particle surface.
[0086] (2) Characterization of average particle size and particle size distribution The particle size distribution of fumed silica suspensions before and after modification was tested using the dynamic light scattering (DLS) principle. The average particle size (D50) of the samples was obtained and a particle size distribution curve was plotted.
[0087] (3) Microscopic morphology and structural analysis (SEM) A suitable amount of silica sol samples before and after modification were diluted, dropped, dried, and surface-sprayed with gold. Subsequently, the samples were placed under a scanning electron microscope (SEM) to observe the microstructure, aggregation state, and density of the surface coating of the nano-silica particles, and the morphological changes before and after modification were compared.
[0088] The results are shown in the table below: As can be seen from the comparison of the data of Example 1 with Comparative Examples 1 and 2 in the table, the present invention has a significant synergistic effect through "stepwise layered coating of dual modifiers".
[0089] When only a single silane coupling agent, KH792, was added to the system (Comparative Example 1), although the amino group of the coupling agent could provide a positive charge to some extent, the deprotonation of the residual silanol groups on the particle surface (SiO₂) occurred under strongly alkaline conditions (pH=10). - It will neutralize a large number of positive charges, resulting in a Zeta potential of only +5.4mV, which makes it very easy for colloidal aggregation to occur.
[0090] When only the cationic polymer PDADMAC (Comparative Example 2) is added to the system, due to the lack of a covalent anchoring layer, the polymer chains are only physically electrostatically adsorbed on the silica surface. Under highly alkaline conditions, they are easily shielded by counterions in the solvent and desorbed. The zeta potential is only +17.3 mV and they gel rapidly.
[0091] In contrast, Example 1, by first constructing a covalently bonded KH792 layer on the surface of fumed silica using a stepwise method, and then firmly bonding the PDADMAC barrier layer through strong electrostatic attraction, successfully achieved a high positive charge reversal of +77.9 mV under strongly alkaline conditions (e.g., ...). Figure 2 As shown in the figure, it far exceeds the critical value for colloidal stability.
[0092] Depend on Figure 1 It is evident that the modified fumed silica exhibits excellent monodispersity in an alkaline aqueous phase, with its average particle size distribution curve displaying a narrowed single peak, thus avoiding the secondary agglomeration phenomenon commonly observed in ordinary fumed silica. The sample prepared in Example 1 was stored statically for 30 days, and the average particle size change rate on the 30th day was less than 5% compared to the initial particle size. No stratification, sedimentation, or gelation was observed. Figure 1 As shown, this covalently anchored-electrostatically coated double-layer stable structure provides a strong synergistic effect of electrostatic repulsion and steric hindrance, enabling it to exhibit excellent colloidal dispersion stability during the 30-day observation period, proving that the system has excellent long-term dispersion stability.
[0093] Comparing Example 1 and Comparative Example 3 reveals that the order of addition and reaction has a decisive influence on the surface charge state of the final product. Comparative Example 3, which modifies KH792 with monomers in a one-step process, has a Zeta potential of -2.9 mV, making positive charge functionalization impossible. This is because the self-condensation reaction of the silane coupling agent and the steric hindrance competitive adsorption of the polymer monomer during mixing cause severe interference, hindering the effective covalent bonding between the coupling agent and the silanol groups (Si-OH) on the silica surface, resulting in a disordered and defective charge layer on the particle surface. This result fully demonstrates the originality and necessity of the stepwise isothermal process of "first covalent reaction, then electrostatic coating" employed in this invention.
[0094] Comparing Examples 1, 4, 5, 6, and 7, it is evident that reaction temperature and reaction time are the core variables controlling the charge density and stability of the colloidal surface. Effect of reaction temperature: Comparing Example 4 (50°C) and Example 5 (70°C), at the preferred temperature of 70°C, the Zeta potential significantly increased from +43.3 mV to +54.7 mV. This indicates that a higher reaction temperature promotes the dehydration condensation reaction between the silane coupling agent and the silanol groups on the fumed silica surface, thereby increasing the grafting density of the interfacial anchoring layer.
[0095] Comparing Examples 6, 1, and 7, the Zeta potential of the product gradually increased from +55.9 mV to +77.9 mV with increasing reaction time. This indicates that extending the reaction time helps the chemical bonding and surface adsorption processes approach physicochemical saturation, constructing a denser positively charged polymer coating layer, thereby endowing the colloidal system with a higher charge stability value.
[0096] Compared to Comparative Examples 4 and 5, the L-arginine's carboxyl group dissociates in an alkaline environment, causing the system's zeta potential to decrease rather than increase, exhibiting strong negative charge at -30.8 mV and -29.1 mV. Even with the addition of PDADMAC, the antagonistic effect of the small zwitterions prevents it from flipping to a positive charge.
[0097] Comparative Examples 6 and 7 show that the traditional inorganic aluminum salt (AlCl3) modification process performs well in acidic environments, but in strongly alkaline environments (pH=8), inorganic aluminum ions are prone to excessive hydrolysis, forming insoluble white flocculent precipitates of Al(OH)3 or transforming into aluminate (AlO3). 2- This causes the system to lose its positive charge (potential is only +4.78mV or -6.6mV) and triggers severe colloidal aggregation.
[0098] This invention completely overcomes the instability of the traditional modified system under alkaline conditions. By introducing organic polymer electrolytes, the modified silica sol can still maintain extremely high positive charge density and long-term non-settling properties in strongly alkaline systems with pH=10 or even higher.
[0099] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing an alkaline positively charged silica sol, characterized in that, Includes the following steps: S1. Prepare a silica aqueous dispersion by mixing fumed silica with water; S2. Under stirring, the silica aqueous dispersion from step S1 is heated, and N-2-aminoethyl-3-aminopropyltrimethoxysilane coupling agent is added to carry out the reaction. S3. Continue to add cationic modifier to the system from step S2 to carry out the reaction; S4. After the reaction is complete, adjust the pH of the system from step S3 to 8-11 to obtain an alkaline positively charged silica sol.
2. The preparation method according to claim 1, characterized in that, In step S1, the solid content of the silica aqueous dispersion is 8%~15%.
3. The preparation method according to claim 1, characterized in that, In step S2, the silica aqueous dispersion is heated to 50~90℃; The reaction was carried out with N-2-aminoethyl-3-aminopropyltrimethoxysilane coupling agent for 2-5 h.
4. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane coupling agent to fumed silica is 1:30-1:
5.
5. The preparation method according to claim 1, characterized in that, In step S3, the cationic modifier is a polymer containing a quaternary ammonium salt structure or an amino structure.
6. The preparation method according to claim 6, characterized in that, In step S3, the cationic modifier is selected from at least one of polydimethyldiallylammonium chloride, polyethyleneimine, and polyepoxychloropropane-dimethylamine.
7. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of cationic modifier to fumed silica is 1:20-1:
2.
8. The preparation method according to claim 1, characterized in that, Step S3, the reaction time is (2~4) h.
9. The preparation method according to claim 1, characterized in that, In step S4, an inorganic base is added to adjust the pH.
10. An alkaline positively charged silica sol, characterized in that, It is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparation and surface modification of alkaline silicon sol
CN102040868A